2009
DOI: 10.1016/j.drugalcdep.2009.06.015
|View full text |Cite|
|
Sign up to set email alerts
|

Methadone and buprenorphine prescribing and referral practices in US prison systems: Results from a Nationwide Survey

Abstract: Background-More than 50% of incarcerated individuals have a history of substance use, and over 200,000 individuals with heroin addiction pass through American correctional facilities annually. Opiate replacement therapy (ORT) with methadone or buprenorphine is an effective treatment for opiate dependence and can reduce drug-related disease and recidivism for inmates. Provision of ORT is nevertheless a frequently neglected intervention in the correctional setting.Objective and Methods-We surveyed the 50 state; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
189
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 232 publications
(202 citation statements)
references
References 44 publications
(65 reference statements)
5
189
0
8
Order By: Relevance
“…For example, although the concept of narcotic blockade has been repeatedly documented since Vincent Dole's work with methadone in the 1960s (Dole et al, 1966;Kleber, 2007;Tetrault and Fiellin, 2012), less than half of respondents agreed, and 45-56% were uncertain, that agonist medication reduces or blocks the effects of heroin. These responses are consistent with previous findings both in other criminal justice dispensations (Nunn et al, 2009;Friedmann et al, 2012) and among community treatment providers (Kang et al, 1997;Kayman et al, 2006) and serve as a disquieting reminder that the stigma and uncertainty with which the public regards MAT stubbornly prevails even among experienced drug court professionals.. Numerous reasons were cited for why agonist medication was either not available or had limited availability to opioid-dependent drug court participants.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…For example, although the concept of narcotic blockade has been repeatedly documented since Vincent Dole's work with methadone in the 1960s (Dole et al, 1966;Kleber, 2007;Tetrault and Fiellin, 2012), less than half of respondents agreed, and 45-56% were uncertain, that agonist medication reduces or blocks the effects of heroin. These responses are consistent with previous findings both in other criminal justice dispensations (Nunn et al, 2009;Friedmann et al, 2012) and among community treatment providers (Kang et al, 1997;Kayman et al, 2006) and serve as a disquieting reminder that the stigma and uncertainty with which the public regards MAT stubbornly prevails even among experienced drug court professionals.. Numerous reasons were cited for why agonist medication was either not available or had limited availability to opioid-dependent drug court participants.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have found both regional and population density differences in MAT attitudes and use (e.g. Peyton and Gossweiller, 2001;Nunn et al, 2009;Huddleston and Marlowe, 2011), and in the use of heroin and illicit prescription opioids (Rosenblum, et al, 2007). In order to examine attitudinal differences both within state and within urbanicity, three drug courts were selected from each state (150 total), stratified so that for each state, one urban, one suburban, and one rural court were randomly chosen.…”
Section: Sampling Strategymentioning
confidence: 94%
See 3 more Smart Citations